Local treatment for relapsing glioblastoma: A decision-making tree for choosing between reirradiation and second surgery. (January 2021) - Scoccianti, Silvia; Perna, Marco; Olmetto, Emanuela; Delli Paoli, Camilla; Terziani, Francesca; Ciccone, Lucia Pia; Detti, Beatrice; Greto, Daniela; Simontacchi, Gabriele; Grassi, Roberta; Scoccimarro, Erika; Bonomo, Pierluigi; et al.
Graphical abstract: Highlights: Localised recurrent glioblastoma (recGBM) should be considered for local treatment. An overview on the use of reirradiation or second surgery in recGBM is herein provided. A simple and practical algorithm to choose surgery versus RT for recGBM is proposed. Estimation of life expectancy, prognostic score systems and predictive factors, and expected toxicity are its keypoints. Abstract: In case of circumscribed recurrent glioblastoma (rec-GBM), a second surgery (Re-S) and reirradiation (Re-RT) are local strategies to consider. The aim is to provide an algorithm to use in the daily clinical practice. The first step is to consider the life expectancy in order to establish whether the patient should be a candidate for active treatment. In case of a relatively good life expectancy (>3 months) and a confirmed circumscribed disease(i.e. without multiple lesions that are in different lobes/hemispheres), the next step is the assessment of the prognostic factors for local treatments. Based on the existing prognostic score systems, patients who should be excluded from local treatments may be identified; based on the validated prognostic factors, one or the other local treatment may be preferred. The last point is the estimation of expected toxicity, considering patient-related, tumor-related and treatment-related factors impacting on side effects. Lastly, patients with very good prognostic factors may be considered for receiving a combined treatment.